2010
DOI: 10.1021/nn101640r
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Band Gap Energies in Cluster-Assembled Ionic Solids through Internal Electric Fields

Abstract: Assembling ionic solids where clusters are arranged in different architectures is a promising strategy for developing band gap-engineered nanomaterials. We synthesized a series of cluster-assembled ionic solids composed of [As(7)-Au(2)-As(7)](4-) in zero-, one-, and two-dimensional architectures. Higher connectivity is expected to decrease the band gap energy through band broadening. However, optical measurements indicate that the band gap energy increases from 1.69 to 1.98 eV when moving from zero- to two-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 43 publications
(64 reference statements)
4
72
0
Order By: Relevance
“…Changing the assembly from a 0D to a 2D architecture is generally expected to decrease the band gap energy through increased band broadening due to larger coordination; however, we generally observe an increase in band gap energy, as seen in Figure 1. 30 The symbols in Figure 1 mark the character of the cluster building block, and the gold-linked, Zn-and Cd-linked, and M(CO) 3 -bound clusters all show an increase in the band gap energy as the dimensionality of the assembly increases. , but changing the cation results in 0D (5) and 2D (6À8) architectures (Figure 4).…”
Section: Band Gap Energy Tuning: Role Of Internal Electric Fieldmentioning
confidence: 99%
“…Changing the assembly from a 0D to a 2D architecture is generally expected to decrease the band gap energy through increased band broadening due to larger coordination; however, we generally observe an increase in band gap energy, as seen in Figure 1. 30 The symbols in Figure 1 mark the character of the cluster building block, and the gold-linked, Zn-and Cd-linked, and M(CO) 3 -bound clusters all show an increase in the band gap energy as the dimensionality of the assembly increases. , but changing the cation results in 0D (5) and 2D (6À8) architectures (Figure 4).…”
Section: Band Gap Energy Tuning: Role Of Internal Electric Fieldmentioning
confidence: 99%
“…I n superlattices and heterostructures, the Coulombic interaction between adjacent atomic layers of (nominally) charged and/or neutral planes can create internal electric fields [1][2][3] that induce or alter many functional electronic, ferroic and optical properties [4][5][6][7][8][9] . In the majority of atomically layered oxides explored to date, however, the heterostructures are constructed by interleaving two or more bulk materials, often perovskite 'blocks' with well-defined three-dimensional connectivity [10][11][12][13][14][15] .…”
mentioning
confidence: 99%
“…Rarely are the starting oxides natural heterostructures themselves, for example, Aurivillius, Dion-Jacobson or the RuddlesdenPopper (RP) phases. The latter (ABO 3 ) n /(AO) (also denoted as A n þ 1 B n O 3n þ 1 ) RP structure has n ABO 3 perovskite blocks stacked along the [001] direction with an extra sheet of AO rocksalt layers interleaved every n perovskite layers. This geometry disconnects the BO 6 octahedra along one direction and imposes severe constraints on the nearest-neighbour interactions 16 , promoting anisotropy in the structure-derived electronic, transport and magnetic properties, which contrasts sharply with the 3D perovskite analogues [17][18][19][20] .…”
mentioning
confidence: 99%
“…[42] In cluster-assembled materials, we found that the dimensionality of these hierarchical materials could change the band-gap energy through the position of the counterions. [5] This may occur because the field could increase or decrease the energy of the frontier orbitals of the cluster and change the band-gap energy, similarly to what is seen in crystalfield splitting. This internal electric field could cause the band-gap energy of a CAM to be larger than that of the free cluster.…”
Section: Introductionmentioning
confidence: 98%